Perfil dos profissionais que atuam em grupos de convivência em terceira idade : desdobramentos no processo de envelhecimento humano - Vesco, Francieli Dal (2011)
The research purpose was to outline the profile of professionals working in groups of living for the elderly and from this, derive possible developments in the human aging process. Thus, power will help in planning actions, aiming at improving its performance and consequently, improve the quality of life for seniors. To that end, semistructured interviews were conducted with thirteen professionals who work in groups living in the city of Passo Fundo, Rio Grande do Sul Within that set out to search, we found that the design of the profile of professionals in support groups, to seniors tend to be constructed by a sum of constraints. Among them, the academic training, which seems to define the type as well as how to conduct activities in working with the elderly. However, one may add still other aspects that influence the performance of these professionals, among whom there are additional environmental factors, the society in which it appears, cultural, ethical, historical, economic, bureaucratic, genetic, living with the elderly, how they built build your knowledge of human aging, how the professional perceives, sees the working groups, inter-relationships with the elderly living in groups. And these factors do not walk alone, they are interrelated. Furthermore, we noticed that the small number of respondents affects the livelihoods of nearly two thousand elderly, if we consider the social circle of them. But that number could quadruple. , Mutatis mutandis, thirteen employees are able to influence the behavior of approximately eight thousand people. Understand who they are professional and understand how they construct their actions can contribute to the delivery of other activities and possibly add another profile of elderly participants. As a consequence, may result in the inclusion of other professionals in groups of convenience, like psychologists, physicians.